Estimation of age dependent penetrance in facioscapulohumeral muscular dystrophy by minimising ascertainment bias. - Lunt, P W (1989)
In any family study using information gathered retrospectively, the influence of the method of ascertainment on the observed segregation ratio in sibships needs careful consideration. The study of kindred members from outside the area of primary ascertainment is invaluable in providing segregation data with minimal ascertainment bias. For facioscapulohumeral muscular dystrophy (FSHD), using this approach, and based on the presence or absence of characteristic clinical signs rather than on an historical account of age at onset, estimates were derived for penetrance of the FSHD gene of less than 5% for ages 0 to 4 years, 21% for ages 5 to 9, 58% for ages 10 to 14, 86% for ages 15 to 19, and 95% penetrance for age 20 years and over. No difference between families was identified. These figures should facilitate genetic counselling and the interpretation of genetic linkage study results in FSHD.